2022
DOI: 10.1097/htr.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Adherence to Concussion Clinical Care Recommendations in a Pediatric Population

Abstract: Objective: To characterize the relationship of sociodemographic factors to adherence to provider recommendations for pediatric concussion. Setting: Primary care (PC) practices within the Children's Hospital of Philadelphia network. Participants: Patients aged 5 to 18 years old who presented to any PC site for concussion from September 26, 2019, to December 31, 2019. Design: Retrospective medical record review. Main measures: The primary outcome was adherence to follow-up recommendations as defined by (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…However, some patients experience barriers to access these therapies throughout their full course of care. Mohammed and colleagues (14) found that disparities are evident when examining adherence to concussion care recommendations, some of which may be addressed by using a cost-effective and equitable at-home program. Our findings indicate at-home exercise programs prescribed within 28 days of injury may be effective in reducing overall concussion symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some patients experience barriers to access these therapies throughout their full course of care. Mohammed and colleagues (14) found that disparities are evident when examining adherence to concussion care recommendations, some of which may be addressed by using a cost-effective and equitable at-home program. Our findings indicate at-home exercise programs prescribed within 28 days of injury may be effective in reducing overall concussion symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Current concussion consensus statements recommend a multi-faceted approach to concussion management (3), particularly in pediatric patients due to an increased vulnerability to injury (4), longer average recovery (5), and the inclusion of additional stakeholders (i.e., school nurses, teachers, parents) (5) relative to adult patients. Additionally, active rehabilitation programs, including vision and vestibular therapies, are recommended for the treatment of adolescent concussion (3,(6)(7)(8); however, barriers to specialized concussion care, including financial barriers (9,10), access to health care (11), or socioeconomic health disparities (12)(13)(14), prevent patients from accessing the relevant concussion care to optimize their recovery. There is a need to further explore cost-effective and equitable approaches to active concussion management in a pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Members of latent classes characterized by greater systematic disadvantage (eg, minoritized racial/ethnic group; older age) were less likely to access inpatient rehabilitation and were at greater risk for mortality. Finally, Mohammed et al 11 examined racial and ethnic disparities in adherence to primary care provider recommendations for concussion in the pediatric population. They found that non-Hispanic Black patients and those who did not have private insurance were less likely to adhere to recommendations relative to non-Hispanic White patients and those with private insurance.…”
Section: Racial Disparitiesmentioning
confidence: 99%
“…For example, several studies revealed racial disparities in TBI care and outcomes. 7,8,10,11 However, race and ethnicity are socially constructed categories that serve as surrogate measures of historical and structural marginalization that may shape TBI care and recovery in myriad, dynamic, and mutually reinforcing ways. 20 As such, including indicators of race and ethnicity alone may be necessary, yet insufficient, for understanding the specific mechanisms underlying disparities in TBI service delivery and recovery.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation